Flash of genius [videorecording (DVD)] - Abraham, Marc, 1949 May 28-; Kinnear, Greg, 1963-; Graham, Lauren, 1967-; Alda, Alan, 1936-; Seabrook, John (Universal Studios Home Entertainment, 2009)
Based on the true story of Robert Kearns. The Kearns' were a typical 1960s Detroit family. Bob is a college professor and part-time inventor. When Bob invents a device that would eventually be used by every car in the world, the Kearns' think they have struck gold. But their aspirations are dashed after the auto giants, who originally embraced Bob's creation, unceremoniously shuns him. Ignored, threatened and then buried in years of litigation, Bob is haunted by what was done to his family and their future. He becomes a man obsessed with justice and the conviction that his life's work, or anyone else's for that matter, should be acknowledged by those who stood to benefit. He and his family pay the toll for refusing to compromise his dignity.